Derozio, poet of India the definitive edition - Derozio, Henry Louis Vivian 1809-1831 (Oxford Univ. Press, 2008)
section 1. The India gazette poets and prose -- section 2. Two volumes, 1827 and 1828 -- section 3. The years 1829-31 -- section 4. Posthumous publications